Charismatic Kyai Leadership and Its Relationship to the Character Building of Santri at Islamic Boarding Schools in Plered Purwakarta District - Wilam Nafilah Robaeah; Irawan Irawan; Tatang Muh Nasir (Pendidikan Agama Islam STIT Palapa Nusantara, 2023)
This research departs from a kiai leadership in Islamic boarding schools which can be said to be the central point. Kiai has full power in regulating and determining policies for every activity in the pesantren, either directly or indirectly. Currently moral degradation is increasingly visible among students. In taking the sample, the researcher used a random sampling technique, which is a random sampling technique from the existing population. Researchers distributed 70 sample questionnaires from a total population of 239, using a Likert scale model questionnaire as primary data which was distributed online using Whats App and Instagram. This study aims to describe (a) the leadership of the clerics in Islamic boarding schools in Plered sub-district, Purwakarta (b) the formation of the character of the students at the Minnatul Huda Islamic Boarding School, (c) the relationship between the kyai leadership and the character building of students in Islamic boarding schools in the Plered sub-district, Purwakarta. From the results of the study, it was concluded that there is a relationship between the cleric's leadership and the formation of the character of the santri in Islamic boarding schools in the Plered Purwakarta sub-district, obtaining a correlation coefficient of 0.588, meaning that the level of strength of the relationship between the kyai's leadership variables and the formation of the character of the santri is 58%, which is interpreted as an entry coefficient price. category 0.40 - 0.59 which is enough. The value of the coefficient of determination (R Square) is 0.346, meaning that the formation of the character of the santri has something to do with the leadership of the cleric of 34.6%, while the rest is related to other factors outside the research. Thus it can be concluded that Ha is accepted in the sense that there is a positive and unidirectional relationship between the leadership of the kiai and the formation of the character of the students at Islamic boarding schools throughout the Plered District, Purwakarta.